Monte Carlo simulation on thickness dependence of hysteresis properties in Ising thin-films - Yongyut Laosiritaworn (2018)
In this work, Monte Carlo simulation was used to model the dynamic hysteresis behavior of ferromagnetic Ising thin-films using the spin-flip algorithm. The purpose is to investigate the thickness dependence of ferromagnetic hysteresis properties while varying frequency and amplitude of the external field. From the results, with increasing the films thickness, the calculated hysteresis properties significantly change due to the stronger ferromagnetic coupling in thicker films. In addition, the universal power law relations among the hysteresis properties, the thickness and the field parameters were found. The scaling exponents were also reported which agree well with a previous experiment on ferromagnetic thin-films. © 2009 Elsevier B.V. All rights reserved.